ANALISIS FLEKSIBILITAS SUPPLY CHAIN PERUSAHAAN ROKOK PR LEE CHOIR DI SIDOARJO - Widayati, Endang Puji (JURNAL TEKMAPRO, 2009)
ABSTRACT Â Industrial competition that moving faster and taft will created a lot of uncertainty. It is mostly happen related customer demand to the product they needed. Availability of material which needed in production of material, the change which related condition and company internal fasility also the change that coming from enviroment or external system of manufacture. To solved this problem we need all element of supply chain and make analysis of supply chain flexibility using analytical hierarchy process (AHP) to know all of the element related with supply chain. This research aim to the company performance identify.Key performance indicator based on main dimention of supply chain flexibility thay are delivery system, production system, product design and supplier system.Itâs divided into 24 (twenty four) key performance indicator. Based on the research result which has been done using concept analytical hierarchy process (AHP) obtained weight for each dimention that are, delivery system (0,365), production system (0,281), product design (0,175) and supplier system (0,258). The flexibility of supply chain level for each dimention thay are, delivery system (91%), production system (93%), product design (91%) and supplier system (97%). And after doing for their analysis, it has been already got five key performance indicator which have main priority to be improved namely, full fill the demand more than one distributor, using general component material testing quickly, using all kind of transportation system and sending demand information quickly. Key word : Flexibility measurement, supply chain, servqual, analytical hierarchy process.